The Common as Cultural Action: new arrangements for a politics of the culture - Monteiro, Rodrigo dos Santos; Greiner, Christine (Revista Brasileira de Estudos da Presença, 2022)
The article aims to observe the rising of new ways of dealing with Brazilian cultural policy, which began to be tested in the last decade and in the current days become more critical due to the cut of Ministry of Culture in 2019. The Festival Olhares Sobre o Corpo, the actions of the collective Estopô Balaio and the Trupe da Lona Preta were analyzed. To collaborate with the debates that, like the selected experiences, problematize the recent decisions of the State; the concept of commonism as cultural action is presented. This is a proposal still little researched at the Brazilian universities. Therefore, it could open new ways to think about the relation between culture politics and collective action.